2019
DOI: 10.1111/clr.416_13509
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and biological complications after implantoplasty – A systematic review

Abstract: Background : Implantoplasty, i.e., the mechanical modification of the implant, including thread removal and surface smoothening, has been proposed during surgical peri-implantitis treatment. Currently, there is no comprehensive appraisal of the literature regarding any potential mechanical and or biological complications after this approach.Aim/Hypothesis : The aim of the current review was to systematically assess the literature to answer the focused question ìAre there any mechanical and or biological compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…However, in a recent systematic review that summarized all laboratory, preclinical in vivo, and clinical research on IP (Stavropoulos et al, 2019), no remarkable mechanical or biological complications associated with IP, in the short-to medium-term, were identified. Only a single case of mucosal tattoo due to the titanium particle debris generated during IP was reported in one of the studies included in this review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a recent systematic review that summarized all laboratory, preclinical in vivo, and clinical research on IP (Stavropoulos et al, 2019), no remarkable mechanical or biological complications associated with IP, in the short-to medium-term, were identified. Only a single case of mucosal tattoo due to the titanium particle debris generated during IP was reported in one of the studies included in this review.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent laboratory study demonstrated that IP significantly reduced the maximum implant failure strength, irrespective of implant type/design, diameter, or material, but in general, the maximum implant failure strength remained high (Bertl et al, 2021). However, in a recent systematic review that summarized all laboratory, preclinical in vivo, and clinical research on IP (Stavropoulos et al, 2019), no remarkable mechanical or biological complications associated with IP, in the short‐ to medium‐term, were identified. Only a single case of mucosal tattoo due to the titanium particle debris generated during IP was reported in one of the studies included in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IP is a common procedure that consists of polishing rough implant surfaces outside the bony envelope, making them less prone to bacterial accumulation, as surface roughness may be risk factor for peri-implant disease. IP is effective in the long term for arresting bone loss caused by PI, both alone and in combination with surgical regenerative procedures and does not seem to be associated with any biological or mechanical complication of importance [9][10][11][12][13]. However, thermal increases during the procedure that could affect the bone, lower resistance to fractures due to reducing the thickness of the implant walls, and the local and systemic biological repercussions that the dispersion of titanium particles might have in the long term have been signaled as potential problems of IP performance [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…IP is a common procedure that consists of polishing rough implant surfaces outside the bony envelope, making them less prone to bacterial accumulation as surface roughness may be risk factor perimplant disease. IP is effective in the long term to arrest bone loss caused by PI, both alone and in combination with surgical regenerative procedures [10][11][12][13] and does not seem to be associated with any biological or mechanical complication of importance [14].…”
Section: Introductionmentioning
confidence: 99%